(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
عادة ما تحمى أنابيب النفط والغاز المطمورة بالتربة، بوساطة طبقة ثخينة من مواد عضوية بوليميرية، ويكمّل هذا الأجراء بحمايتها بنظام الحماية المهبطيه. تسمح هذه الحمايات المضاعفة بحماية انابيب النفط والغاز من التآكل. ولكن بالرغم من كل هذا، فإن وجود انابيب النفط والغاز القريبة من مصدر الحقول الكهرومغناطيسية، مثل خطوط التوتر العالي فإن عملية التآكل تحصل في الشقوق والثقوب الناشئة على طبقة العزل، تدعى هذه العمليةالتآكل بالتيار المتناوب (AC Corrosion). يتأثر هذا النوع من التآكل ببعض البارامترات مثل مطال التيار المتناوب المحّرض على سطح المعدن ، بالإضافة الى شدة تيار الحماية المهبطيه المطبق، وكذلك دور التربة ونوعها. تمت دراسة هذا النوع من التآكل نظريا وعمليا باستخدام قطع من الفولاذ الكربوني المستخدم في الصناعة النفطية. واستخدم محلول يحاكي التربة التي يطمر بها هذا الانبوب، ودرست هذه الظاهرة من خلال تجارب عدة. تم تحليل مركبات التآكل الظاهرة على سطح المعدن، وأظهرت ان تواتر 50Hzيمكن ان يكون سريعا جدا بالمقارنة مع زمن حدوث التآكلالطور الموجب و السالب بالنسبة للتيار المتناوب و أظهرت النتائج التي تم الحصول عليها وجود تأثير هام لمطال التيار المتناوب المحّرض ومقاومة التربة Oil and gas buried pipeline are usually protected by a thick organic coating and supported by a cathodic protection system. The protection process allows the pipe line protection against corrosion; however, corrosion is taken place in the cracks and holes of insulation coating due to pipelines adjacency to electromagnetic fields. The process is called AC corrosion affected by some parameters such as AC induced amplitude, cathodic current protection and soil type. This corrosion was theoretically and practically studied by using carbon steel pieces. In addition, a solution stimulating the soil where the pipelines are buried was used. This phenomenon was studied through several experiments. Corrosion compounds were also analyzed. The results revealed a significant effect of AC induced amplitude and soil resistance. It has been also shown that 50 Hz frequency can be very quick in comparison with corrosion occurrence time at each positive or negative AC current phase.